RECHARGEABLE ALLUMUNIUM ION (Al-ion) BATTERY WITH BASIC MATERIAL ACTIVATED COCONUT SHELL CHARCOAL - Sri Wahyuni; Fitriah (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2018)
This study aims to know the tecnique of making of rechargeable Al-ion battery with basic material activated coconut shell charcoal and to know the best composition of materials to produce optimum potential (V) and current (mA). The working principle of battery using electrochemical process to produce potential (V) and electric current (mA). In wich principle is indeed involves only the transport of elecrtons beetween two electodes separated by a conductive medium (electrolyte). There are two electrodes used in which aluminum as anode undergoes oxidation reaction and graphite as cathode undergoes reduction reaction. The optimum composition in the production of Al-ion batteries with basic marerial activated coconut shell charcoal is 7,5 grams activated coconut shell charcoal, 2,5 grams polypyrol catalyst (MnO2), and NaCl 4,5 %. This composition produce 2,05 mA at the first hours as optimum current capacity the first hour of 45 mA because the remaining wet condition of electrolyte at this point allows the electrons to move easily. For the value of the optimum voltage in the last hours is a discharge voltage of 2,05 volts and superfast charging time is only one minute.